Introduction of Forehead Lesion Assessment with House-Brackmann Score for Facial Nerve Paralysis Evaluation - Wan Syahirah, Wan Samsudin; Rosdiyana, Samad; Sundaraj, Kenneth; Mohamed, Rizon; Mohd Zaki, Ahmad (ICAROB2020, 2020)
This paper present a novel approach of forehead lesion assessment using Gabor filter method to identify the type of facial nerve paralysis and proposed a forehead-HB score table to assist the clinicians in assessing the facial nerve function quantitatively, quicker and in a convenient way. A 100% of accuracy has been obtained in identifying the two type of facial lesion, Upper Motor Neuron (UMN) and Lower Motor Neuron (LMN) lesion. Increasing more data may enhance the performance of the accuracy